Pre-weaning growth performance of Etawah Crossbred goats fed milk replacer - ., Supriyati (Indonesian Animal Sciences Society, 2012)
In this experiment the effect of feeding milk replacer and dairy milk on the growth performance of pre-weaning of Etawah Crossbred goats was studied. Thirty eight heads of pre-weaning of Etawah Crossbred kids were divided into 2 groups, Group A receiving dairy milk and Group B receiving formulated milk replacer. All kids were fed with colostrum at the first 3 days. The milk replacer was formulated from skim milk, cassava flour, soy flour, corn flour, vitamin, mineral, salt and amino acids (lysine and methionine). The milk replacer was diluted ten times with warm water, then probiotic and sugar were added. The pre-weaning kids fed 300-600 ml milk twice a day, in the morning and in the afternoon. The liveweight of pre-weaning kids were measured every 2 weeks. The experiment was carried out for 12 weeks. The parameter measured were nutrient intakes, ADG and mortality rate. Data was analysed by T test. The proximate analysis results of milk replacer were DM 93.50%, CP 22.20%, Fat 4.62%, GE 3869 kcal/kg, CF 1.31%, ash 4.22%, Ca 0.60% and P 0.46%. The DM and CP intakes were 111.98 and 28.93 g/d; 97.31 and 23.10 g/d, with ME 659 and 379 kcal/kg for group A and B, respectively. The ADG of pre-weaning kids for Group A and B were significantly different (P < 0.05) which were 96.03 Â± 11.83 and 83.62 Â± 16,34 g/d; mortality rates were 0% and 10% for group A and B, respectively. It is concluded that the rate of the pre-weaning kids of Crossbred Etawah goat fed formulated milk replacer grew slower than kids receiving dairy milk. Key Words: Milk Replacer, Pre-Weaning, Growth, Crossbred Etawah Goats